Influence of TMPRSS6 genotype on iron status parameters in stable COPD patients - Trtica, Marko; Novaković, Ivana; Dopsaj, Violeta; Milenković, Branislava; Janković, Jelena; Dimić Janjić, Sanja; Dopuđa Pantić, Vesna; Martinović, Jelena; Jovičić, Snežana (Journal of Medical Biochemistry, 2024)
Background: The SNP rs855791 has been linked to increased hepcidin levels, variations in serum iron, transferrin saturation and red blood cell indices. Our goal was to determine the prevalence of this polymorphism among COPD patients and to assess its impact on iron status parameters including hepcidin in patients with stable COPD. Methods: We analysed iron status parameters and genetic data form 94 COPD patient: 29 patients with wild-type genotype (WT group) and 65 patients with either homozygous or heterozygous genotype (HH group). Additionally, the prevalence of SNP rs855791 was assessed in 192 volunteers. Results: The frequency distribution of SNP rs855791 was comparable between the COPD patients and control subjects (p=0.791). Iron status parameters were within their respective reference values and did not show neither statistically nor clinically significant difference between the WT and HH group of COPD patients. However, after excluding patients with (sub)clinical vitamin B12 deficiency and/or hypoxemia, WT group of patients exhibited significantly lower erythropoietin levels (p=0.015). The area under the curve for EPO was 0.688 (95% CI: 0.545-0.830, p=0.015), with an optimal cut-off of 9.74, sensitivity of 61.2% (95% CI: 58.1-64.3) and specificity of 65.0% (95% CI: 61.8-68.3). Conclusion: In patients with stable COPD, iron status parameters do not differ between WT and HH group of patients. After excluding those with (sub)clinical vitamin B12 deficiency and/or hypoxia, only statistical and not clinical difference in EPO levels was observed suggesting that EPO may regulate hepcidin levels and thus influence the development of iron deficiency and/or anaemia.